Performance analysis of coded 8-pssk system with MRC diversity in fading channels - Young Chun, Jae; Soo Yeom, Kee; Gon. Kim, Eon. (International Journal of Engineering and Technology, 2018)
Due to the increasing demand for low power communication in the field of remote control & monitoring, it is necessary to introduce a communication technique to meet the various QoS requirements even in an inferior radio channels. In order to ensure these QoS requirements, we propose a communication technique that applies the channel code, diversity scheme into power-efficient modulation. It makes the radio possible to dramatically improve BER by reducing the uncertainty due to fading channels. A core of proposed communication technique is to maximize the performance gain by adopting diversity technique and channel coding scheme. Diversity gain and channel coding gain further increase the performance difference (gain) between power-efficient modulation and conventional modulation, resulting in a signification BER improvement. By adapting the proposed communication technique it is expected to improve the usability of low-power radio according to the satisfaction of the various QoS requirements.Â Â
Keywords: PSSK Modulation; Convolution Code; MRC Diversity; Rican Fading; Power Efficiency.